Do foreign players change the nature of the game among local entrepreneurs? - Mika Maliranta; Satu Nurmi (The Research Institute of the Finnish Economy (ETLA), 2004)
The effect of foreign-owned companies on entrepreneurial survival in the Finnish business sector is analyzed by using a new, exceptionally rich linked data on employees, entrepreneurs and their companies. Our new indicator of foreign presence, based on the observed spatial scopes of the local labor markets, outperforms other commonly used alternatives for measuring regional effects. According to the results, foreign-owned companies crowd out local entrepreneurship. They increase competitive pressure in a way that selects efficient entrepreneurs from inefficient ones, which stimulates productivity-enhancing restructuring at the micro-level. In contrast to the theoretical prediction, higher education does not seem to make entrepreneurs less vulnerable to the foreign presence despite their possibly higher ability to adopt knowledge from foreign-owned companies. – – Ulkomaalaisten yritysten vaikutusta yrittäjien jatkamistodennäköisyyteen Suomen yritystoiminnassa on tutkittu käyttämällä uusia ja poikkeuksellisen arvokkaita yhdistettyjä aineistoja palkansaajista, yrittäjistä ja heidän yrityksistään. Tutkimuksessa käytetään uutta ulkomaalaisten yritysten läsnäolon intensiteetin mittaa, joka pohjautuu havaittuihin työssäkäyntialueisiin. Uusi indikaattori näyttää toimivan paremmin kuin perinteiset tavat tutkia alueellisia vaikutuksia. Tulosten mukaan ulkomaalaiset yritykset syrjäyttävät paikallista yrittäjyyttä. Ne lisäävät kilpailupainetta niin, että tehokkaat yrittäjät valikoituvat tehottomista. Näin ne lisäävät alueiden tuottavuutta vahvistavaa mikrotason rakennemuutosta. Teoreettisten ennusteiden vastaisesti yrittäjän hyvä koulutus ei sinänsä näytä tekevän hänestä vähemmän altista ulkomaalaisten yritysten syrjäyttävälle vaikutukselle, vaikka koulutuksen voisi odottaa parantavan kykyä omaksua ulkomaalaisista yrityksistä leviävää tietämystä.
Keywords: F23; L10; M13; O31; R11; R23; 330; Foreign ownership; entrepreneurship; local labor markets; competition; survival; company efficiency; selection effect; absorptive capacity; Ulkomaalaisomistus; yrittäjyys; kilpailu; eloonjääminen; yrityksen tehokkuus; valikoitumisvaikutus; omaksumiskyky; Multinationales Unternehmen; Regionales Wachstum; Unternehmen; Unternehmensentwicklung; Marktstruktur; Innovation; Schätzung; Finnland